A fear memory engram and its plasticity in the hypothalamic oxytocin system - Hasan, Mazahir; Althammer, Ferdinand; Silva da Gouveia, Miriam; Goyon, Stephanie; Eliava, Marina; Lefevre, Arthur; Kerspern, Damien; Schimmer, Jonas; Raftogianni, Androniki; Wahis, Jerome; Knobloch-Bollmann, Hanna Sophie; Tang, Yan; et al. (Neuron, 2019)
Oxytocin (OT) release by axonal terminals onto the central nucleus of the amygdala exerts anxiolysis. To investigate which subpopulation of OT neurons contributes to this effect, we developed a novel method: virus-delivered genetic activity-induced tagging of cell ensembles (vGATE). With the vGATE method, we identified and permanently tagged a small subpopulation of OT cells, which, by optogenetic stimulation, strongly attenuated contextual fear-induced freezing, and pharmacogenetic silencing of tagged OT neurons impaired context-specific fear extinction, demonstrating that the tagged OT neurons are sufficient and necessary, respectively, to control contextual fear. Intriguingly, OT cell terminals of fear-experienced rats displayed enhanced glutamate release in the amygdala. Furthermore, rats exposed to another round of fear conditioning displayed 5-fold more activated magnocellular OT neurons in a novel environment than a familiar one, possibly for a generalized fear response. Thus, our results provide first evidence that hypothalamic OT neurons represent a fear memory engram.